Gerontomarketing on the Russian Banking Services Market: Problems and Prospects - Julia ASTASHOVA; Antonina UKHOVA; Yana DOBRYNINA; Sergey KALENTEEV (Communications of International Proceedings, 2021)
The study, the results of which are presented in the paper, is aimed at studying the practice of spreading gerontomarketing in the Russian banking market. The banking services market, along with the leisure market and the medical services market, according to the authors’ hypothesis, due to their significant contribution to the implementation of the strategy of active aging, have a high potential for gerontological orientation. The article presents the results of a study of the banking services sector from the standpoint of the practice of using gerontomarketing tools: the main trends in the development of the market are outlined, leaders in the market for working with the gerontosegment are identified, the problems of using gerontomarketing in the practice of Russian banks are systematized. The research results can be used in the development strategies for both individual banks and the banking sector as a whole.
Keywords: Gerontomarketing; Banking Services Market; Market Gerontological Orientation.